Rent-seeking Contests under Symmetric and Asymmetric Information - Cédric Wasser (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We consider a variant of the Tullock rent-seeking contest. Under symmetric information we determine equilibrium strategies and prove their uniqueness. Then, we assume contestants to be privately informed about their costs of effort. We prove existence of a pure-strategy equilibrium and provide a sufficient condition for uniqueness. Comparing different informational settings we find that if players are uncertain about the costs of all players, aggregate effort is lower than under both private and complete information. Yet, under additional assumptions, rent dissipation is still smaller in the latter settings. Numerical examples illustrate that there is no general ranking between private and complete information. The results depend on the distribution costs are drawn from and on the exact specification of the contest success function.
urn:nbn:de:bvb:19-epub-13243-9
Keywords: D72; D74; D82; C72; 330; Rent-seeking; Contest; Asymmetric Information; Private values; Auktionstheorie; Rent-Seeking; Asymmetrische Information; Theorie